2015
DOI: 10.1038/tp.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived flavanol (−)epicatechin mitigates anxiety in association with elevated hippocampal monoamine and BDNF levels, but does not influence pattern separation in mice

Abstract: Flavanols found in natural products such as cocoa and green tea elicit structural and biochemical changes in the hippocampus, a brain area important for mood and cognition. Here, we evaluated the outcome of daily consumption of the flavanol (−)epicatechin (4 mg per day in water) by adult male C57BL/6 mice on measures of anxiety in the elevated plus maze (EPM) and open field (OF). Furthermore, pattern separation, the ability to distinguish between closely spaced identical stimuli, considered to be mediated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 87 publications
1
37
1
Order By: Relevance
“…In agreement with this, many other in vivo studies suggest that not only blueberry-flavonoids (7,8,10,114,116,117), but also pure anthocyanins (8), (-) epicatechin (67,121), fisetin (122), fustin (123), EGCG (124,125) can modulate hippocampal ERK, Akt and CREB activation as well as protein and mRNA BDNF levels ( Table 1). More detailed studies further indicate increases in BDNF mRNA expression in specific regions of the hippocampus, such as DG and CA1 following flavonoid-rich blueberry interventions (7,8).…”
Section: Flavonoid Modulation Of Synaptic Plasticity: Insights From Asupporting
confidence: 76%
See 1 more Smart Citation
“…In agreement with this, many other in vivo studies suggest that not only blueberry-flavonoids (7,8,10,114,116,117), but also pure anthocyanins (8), (-) epicatechin (67,121), fisetin (122), fustin (123), EGCG (124,125) can modulate hippocampal ERK, Akt and CREB activation as well as protein and mRNA BDNF levels ( Table 1). More detailed studies further indicate increases in BDNF mRNA expression in specific regions of the hippocampus, such as DG and CA1 following flavonoid-rich blueberry interventions (7,8).…”
Section: Flavonoid Modulation Of Synaptic Plasticity: Insights From Asupporting
confidence: 76%
“…Effects on neurogenesis have proven scarce with, for example, (-) epicatechin supplementation showing consistently no effects on the number of newly formed neurons (11,121). However, an effect on survival of new neurons rather than increases in neurogenic rates, might be an alternative mechanism by which flavonoids can affect hippocampal function.…”
Section: Flavonoid Modulation Of Synaptic Plasticity: Insights From Amentioning
confidence: 99%
“…Two-week cocoa polyphenolic extract treatment had an antidepressant-like effect in Wistar-Unilever rats subjected to a forced-swim test without accompanying changes in locomotion in the OF [67]. In adult C57BL/6 mice, Epi had an anxiolytic effect as represented by an elevated ratio of distance traveled and time spent in the central zone of the OF compared to periphery [68]. However, it has to be noted that all of these studies were performed in normotensive rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, a large part of polyphenols obtained from plants, are speculated to be effective in the treatment of several CNS disorders such as depression (Donato et al 2014, Souza et al 2013). In addition, evidence suggests that natural products rich in flavonoids, which increase the BDNF levels, are promising therapeutic targets for the treatment of depression (Stringer et al 2015). Van Praag et al (2007) showed that consumption of (−)-epicatechin increases memory function, hippocampal angiogenesis, and neuronal spine density.…”
Section: Resultsmentioning
confidence: 99%